Design and Preparation of Lignin‐Based Hierarchical Porous Carbon Microspheres by High Efficient Activation for Electric Double Layer Capacitors. Issue 15 (22nd May 2018) - Zhang, Yang; Yu, Baojun; Zhang, Jie; Ding, Xiaohui; Zeng, Jingxuan; Chen, Mingming; Wang, Chengyang
Abstract: Activated carbon materials are typically used for electric double layer capacitor (EDLC) electrodes due to their high specific surface area. However, designing the pore structure and improving the efficiency of activation have been required, as activated carbon materials often need to have a rapid charge/discharge rate performance and a high powder density. In this work, lignin‐based hierarchical porous carbon microspheres (HPCMs) were designed and prepared through inverse phase dehydration to shape spherical morphology. In addition, K2 CO3 as a pH regulator is premixed with lignin, and subsequently acted as the mesopore template and activating agent to fulfil highly efficient activation. The mass ratio of K2 CO3 to lignin was controlled below 0.75. By applying to supercapacitor devices, the current HPCMs exhibited a remarkable capacitance and rate performance of 140 F g −1 at 0.05 A g −1 in organic electrolyte. Moreover, the performance can even remain 100 F g −1 even at 10 A g −1 . The current study therefore demonstrated that the premixing of activating agent greatly improves the efficiency of activation, as K2 CO3 successfully reacts with lignin molecules and forms channels inside spheres. As a result, the inverse phase dehydration of lignin and K2 CO3 provides a new approach for preparing electrode materials with suitable pore structure in high efficient activation, and to our knowledge, there is no report that can prepare activated carbon in such electrochemical performance with a mass ratio of activating agent to precursor lower than 1 by chemical activation. Abstract : A new (micro) ball game : Lignin‐based hierarchical porous carbon microspheres showing a spherical morphology are designed and prepared through inverse phase dehydration. K2 CO3 as a pH regulator is premixed with lignin, which acts as the mesopore template and activating agent high efficiencies in energy storage devices.